2010
DOI: 10.5271/sjweh.2985
|View full text |Cite
|
Sign up to set email alerts
|

The impact of junior doctors’ worktime arrangements on their fatigue and well-being

Abstract: Objective Many doctors report working excessively demanding schedules that comply with the European Working Time Directive (EWTD). We compared groups of junior doctors working on different schedules in order to identify which features of schedule design most negatively affected their fatigue and well-being in recent weeks. MethodsCompleted by 336 doctors, the questionnaires focused on the respondents' personal circumstances, work situation, work schedules, sleep, and perceptions of fatigue, work-life balance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 22 publications
3
40
2
Order By: Relevance
“…Performing the same amount of work in fewer hours (work compression) is of concern regarding workload44 and overall well-being,45 and may place trainee doctors at risk of burnout 46. Although much of the literature relating to fatigue comes from the USA where restricted working hours are still much longer than in Europe (eg, 80 h/week and longer maximum shift lengths), two UK self-report studies conducted shortly after implementation of the 48 h working week have highlighted the effect of different schedules on fatigue, including the negative effect of working 7 consecutive nights, having only 1 day of rest after night shifts, intervals of less than 10 h between shifts, and shifts of 12 consecutive days 30 31. Difficulty achieving naps during night shifts, and poor provision for naps, has been reported elsewhere 33.…”
Section: Discussionmentioning
confidence: 99%
“…Performing the same amount of work in fewer hours (work compression) is of concern regarding workload44 and overall well-being,45 and may place trainee doctors at risk of burnout 46. Although much of the literature relating to fatigue comes from the USA where restricted working hours are still much longer than in Europe (eg, 80 h/week and longer maximum shift lengths), two UK self-report studies conducted shortly after implementation of the 48 h working week have highlighted the effect of different schedules on fatigue, including the negative effect of working 7 consecutive nights, having only 1 day of rest after night shifts, intervals of less than 10 h between shifts, and shifts of 12 consecutive days 30 31. Difficulty achieving naps during night shifts, and poor provision for naps, has been reported elsewhere 33.…”
Section: Discussionmentioning
confidence: 99%
“…The trainees had to complete the course in their spare time, and weekly work hours > 48 h for junior doctors are associated with work-life interference [27]. The European Working Time Directive (EWTD) has made standards for weekly work hours for junior doctors to limit incidents at work [28].…”
Section: Discussionmentioning
confidence: 99%
“…2 For example, working more frequent on-calls (either at weekends or during the week) was associated with increased psychological strain and work-life interference, while being restricted to only one rest day after working nights was associated with greater fatigue. In support of the EWTD stipulations, we found that working Ͼ48 hours per week and short rest inter-shift intervals were both independently associated with increased fatigue.…”
Section: Andrew Rl Medfordmentioning
confidence: 99%
“…Indeed, recent research into the use of reliability suggests that the standard error of measurement may be a more appropriate metric. 2 Nevertheless, it is reassuring that in nine out of 11 SCE diets to date reliability values have exceeded 0.8.…”
mentioning
confidence: 99%